Impetigo herpetiformis: an unknown dermatosis of pregnancy - Khouna, Afaf; Dikhaye, Siham; Zizi, Nada (International Journal of Scientific Reports, 2020)
Impetigo herpetiformis or pustular psoriasis of pregnancy is a rare dermatosis of pregnancy that typically starts in the second half of pregnancy and resolves postpartum. It can be life threatening for both mother and fetus and often causes therapeutic problem. We report a case of 37-year-old pregnant woman with history of generalized pustular lesions in the two previous pregnancies, presenting an impetigo herpetiformis during her third pregnancy, resolved one day after the delivery.